The concepts of in-phase multichannel Ka-band HPM oscillators; IEEE International Conference on Plasma Science (ICOPS) - Yalandin M. I. Michael Ivanovich; Rukin S. N. Sergey Nikolaevich; Sharypov K. A. Konstantin Anatolyevich; Shpak V. G. Valery Grigoryevich; Shunailov S. A. Sergei Afanasievich; Ul'maskulov M. R. Marat Rakhmetovich; Rostov V. V. Vladislav Vladimirovich; Klimov A. I. Aleksey Ivanovich (2011, 2011)
Title screen